A skeleton of peat-trapped forest rhinoceros Stephanorhinus kirchbergensis (Jäger, 1839) from Gorzów Wielkopolski, Northwestern Poland: a record of life and death of the Eemian large mammals - Stefaniak, Krzysztof; Kotowski, Adam; Badura, Janusz; Sobczyk, Artur; Borówka, Ryszard Krzystof; Stachowicz-Rybka, Renata; Moskal-del Hoyo, Magdalena; Hrynowiecka, Anna; Tomkowiak, Julita; Sławińska, Joanna; Przybylski, Bogusław; Ciszek, Dariusz; et al. (Neues Jahrbuch für Geologie und Paläontologie - Abhandlungen)
We present a description of an almost complete skeleton of the forest rhino (Stephanorhinus kirchbergensis) found near Gorzów Wielkopolski (Northwest Poland) in its geological and palaeoenvironmental context. While finds of bones and teeth are common, the importance of this find resides in, that it is the most complete specimen of this species, almost perfectly preserved in a wellstudied and dated stratigraphic and sedimentological context, along with other fossil fauna and flora. The OSL dates of glaciofluvial sediments sandwiching skeleton-bearing horizons indicate a Middle Eemian age of the Pleistocene paleolake land. This warm climate is also indicated by the results of sedimentological, geochemical, paleobotanical, and isotopic analyses. The rhino skeleton was deposited in a shallow area near the lake's littoral zone. Bite marks of a large predator (cave hyena) were recognized on the rhino's pelvis, which, due to their location, were probably created post-mortem. With an estimated height of 1.82 m at the withers, this was a large adult Stephanorhinus kirchbergensis. The results of osteometric analyses indicate that we are dealing with one of the largest known individuals of this species. Although it suffered from a pathologically deformed spine, the individual died at a relatively old age